Physical activity-based nutrition educational games interventions for elementary school children - Khasana, Tri Mei; Ngaisyah, Rr Dewi (BKM Public Health and Community Medicine, 2022)
Purpose: An approach that can be used in delivering messages to children is the gamification method or game-based learning. This study aims to determine the effect of physical activity-based nutrition educational games on school children's nutritional status and nutrition knowledge. Methods: This study used a quasi-experimental method with a one-group pretest-posttest with a control design. The intervention group was given physical activity-based nutrition educational games, namely "healthy eating plate" and "healthy food race" for 15 minutes for each game, once a week for nine weeks. Data analysis used paired sample t-test and independent t-test. Results: In the two groups, the anthropometric data differed only on body weight between the pre and post (p=0.000). The nutrition knowledge means score between the pre and post of intervention showed a significant difference (p=0.016) in the intervention group but not in the control group. The physical activity-based nutrition educational games affected body weight (p=0.000) and nutrition knowledge (p=0.016). Conclusion: Physical activity-based nutrition educational games (total duration 30 minutes) for nine weeks can increase nutrition knowledge and maintain normal weight in elementary school children.